The Use of Supplementary Trilingual English-Indonesian-Balinese E-books to Improve Elementary School Students’ English Productive Skills - Dewantara, Kadek Andre Karisma; Adnyani, Ni Luh Putu Sri; Suarcaya, Putu (Universitas Pendidikan Ganesha, 2024)
Although the Merdeka Curriculum provides opportunities for all primary school education units to teach English as an elective subject, the learning process is often not optimal because it is taught by classroom teachers who do not have formal education as English teachers. In addressing this problem, various efforts have been made, one of which is developing trilingual English E-book teaching materials where in the textbook, English material has equivalents in both Indonesian and Balinese. However, in its development stage, this E-book needs to be tested regarding the impact of its use on students' English language skills. Therefore, this study aims to examine the effect of using the Trilingual English-Indonesian-Balinese E-book supplementary book on the productive skills of grade 1 elementary school students. Using an experimental design approach of one group pre-test post-test design as well as purposive sampling, this study involved grade 1 students in Buleleng Regency who were taught by classroom teachers without formal education as English teachers. Data collection used speaking tests for speaking skills and word writing. The data obtained from the pre-test and post-test results were analyzed using Multivariate Analysis of Variance (MANOVA). The results of this study indicate that the use of the supplementary trilingual English-Indonesian-Balinese e-book significantly improves the speaking and writing skills of Grade 1 elementary students. Overall, this study demonstrates that the trilingual e-book has great potential in supporting students' productive skills at the elementary level, particularly in mastering speaking and writing skills.